2021
DOI: 10.1177/10760296211024754
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Significance of miR-675-3p in Patients With Atherosclerosis

Abstract: In recent years, a rising number of studies have confirmed that microRNA (miRNA) plays a prominent role in the early diagnosis and prognostic value assessment of cardiovascular diseases. The current study was conducted to examine the expression of miR-675-3p in atherosclerosis (AS) patients and to evaluate its clinical diagnosis and prognostic value. 110 AS patients and 70 healthy controls were included in the study. Serum miR-675-3p levels were detected by quantitative real-time PCR (qRT-PCR). The clinical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Previous studies have also demonstrated the involvement of these miRNAs in the regulation of lipid accumulation, energy metabolism, production of vascular inflammatory factors, and proliferation, migration, and apoptosis of endothelial and smooth muscle cells (35)(36)(37)(38)(39)(40)(41)(42)(43)(44),indicating their close…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have also demonstrated the involvement of these miRNAs in the regulation of lipid accumulation, energy metabolism, production of vascular inflammatory factors, and proliferation, migration, and apoptosis of endothelial and smooth muscle cells (35)(36)(37)(38)(39)(40)(41)(42)(43)(44),indicating their close…”
Section: Discussionmentioning
confidence: 94%
“…Studies have shown that miR-675-3p (a mature form of miR-675) can promote colorectal cancer and esophageal squamous cell carcinoma and regulate skeletal muscle regeneration and differentiation [ 4 , 5 , 6 ]. Recently, an association between abnormal expression of pre-miR-675 and cardiovascular disease has also been identified [ 7 ]. Elevated levels of pre-miR-675 in the patient serum suffering from atherosclerosis highlight the need to use pre-miR-675 as a new diagnostic biomarker in early diagnosis of cardiovascular disorders [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an association between abnormal expression of pre-miR-675 and cardiovascular disease has also been identified [ 7 ]. Elevated levels of pre-miR-675 in the patient serum suffering from atherosclerosis highlight the need to use pre-miR-675 as a new diagnostic biomarker in early diagnosis of cardiovascular disorders [ 7 ]. Abnormal expression of pre-miR-675 has been linked to various neurological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that miR-675-3p (a mature form of miR-675) can promote colorectal cancer, esophageal squamous cell carcinoma and regulate skeletal muscle regeneration and differentiation [4][5][6]. Recently, association between abnormal expression of miR-675 and cardiovascular disease have also been identified [7]. Elevated levels of miR-675 in the patient serum suffering from atherosclerosis highlights the need to use miR-675 as a new diagnostic biomarker in early diagnosis of cardiovascular disorder [7].…”
mentioning
confidence: 99%
“…Recently, association between abnormal expression of miR-675 and cardiovascular disease have also been identified [7]. Elevated levels of miR-675 in the patient serum suffering from atherosclerosis highlights the need to use miR-675 as a new diagnostic biomarker in early diagnosis of cardiovascular disorder [7]. Abnormal expression of miR-675 has also been linked to various neurological diseases.…”
mentioning
confidence: 99%